Paparan benalu (teh dan mangga) terhadap kadar Superoksida Dismutase (SOD) serum tikus hipertensi model preventif - Mufida, Nur; Sjakoer, Nour Athiroh Abdoes; Mubarakati, Nurul Jadid (Jurnal Biologi Udayana; Vol 26 No 1 (2022): JURNAL BIOLOGI UDAYANA, 2022)
One of the diseases that become a health problem because of the increasing prevalence every year is hypertension. The high of ROS ( Reactive Oxygen Species ) in the body will increase the formation of excess free radicals and make the endogenous antioxidant SOD ( Superoxide dismutase ) be used in excess so that it becomes the cause of the emergence of hypertension. Herbal tea parasite and mango parasite are plants that have the potential to prevent hypertension by increasing SOD activity in the body. The purpose of this study was to determine the effect of exposure to a combination of methanolic extract of tea parasite and mango parasite (CMETMMM) on increasing serum SOD levels in DOCA-salt-induced hypertension rats using a preventive model. In this study, experimental methods were used with 25 male Wistar rats as test animals which were divided into 5 groups and there were 5 rats in each group, namely negative control (K-), positive control (K+), and group with CMETMMM exposure treatment (P1) at a dose of 50 mg/kgBW, (P2) at a dose 100 mg/kgBW, and (P3) at a dose 200 mg/kgBW. The results showed that CMETMMM exposure had an effect on increasing serum SOD activity in hypertensive rats with a significant difference in the mean value between all groups with p-value <0,05. The effectiveness of exposure to tea parasite and mango parasite was controlled by CMETMMM at a dose of 100 mg/KgBW which is an effective dose in increasing SOD serum levels of rats with DOCA-Salt hypertension model.